PERAN STRATEGIS GURU PENGGERAK DALAMKREATIVITAS PEMBELAJARAN BERBASIS PROYEK PADA KURIKULUM MERDEKA DI PENDIDIKAN DASAR - Dameria Sinaga; Melda Rumia Rosmery Simorangkir (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Studies on the role of Guru Penggerak in optimizing the implementation of the Merdeka Curriculum in primary education are essential to obtain empirical insights into the program’s contribution to improving learning quality. This study aims to analyze the strategic role of Guru Penggerak in supporting the implementation of the Merdeka Curriculum, which emphasizes student-centered learning, curriculum flexibility, and the strengthening of character education and 21st-century competencies. This research employed a qualitative method with a descriptive phenomenological approach grounded in the social definition paradigm. The study was conducted at SDN Cakung Timur 09 Pagi, Jakarta, Indonesia. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that Guru Penggerak possess a comprehensive understanding of the concepts and objectives of the Merdeka Curriculum, as reflected in the implementation of project-based learning, differentiated instruction, and the integration of technology in the teaching and learning process. Furthermore, Guru Penggerak actively contribute to creating a conducive learning environment, fostering students’ creativity, and strengthening collaboration and a positive learning culture within the school. These findings affirm that Guru Penggerak play a strategic role as agents of change in optimizing the implementation of the Merdeka Curriculum in primary education.